(3eONd ddJSjjQ hGdYedjGJ GdEOGQjI (B/s - (3Hf MehO, ScjfIs ((3GdLRGFQ (B: s (3TQcI OGQ GdCeI ddWHGYI hGdfTQ hGdJhRjY(B, s, 2012)
(3jVe YehejGJ Mhd WHjYI GdYedjGJ GdEOGQjI, GdeOGQS hGdfXQjGJ GdEOGQjI, GdJNWjW, GdJfXje, GdJhLjg, GdQbGHI, EJNGP GdbQGQGJ(B.s
(3HjHdjhZQGajG(B: (3U U(B.197-199s
Keywords: (3EOGQI GdCYeGds; (3GdJNWjWs; (3GdQbGHI GdEOGQjIs